2010
DOI: 10.1053/j.seminhematol.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab: Mechanism of Action

Abstract: Rituximab is a mainstay in the therapy for a broad variety of B-cell malignancies. Despite its undeniable therapeutic value, we still do not fully understand the mechanisms of action responsible for rituximab's anti-tumor effects. Direct signaling, complement dependent cellular cytotoxicity and antibody dependent cellular cytotoxicity all appear to play a role in rituximab efficacy. In vitro, animal model and clinical data addressing each of these mechanisms of action are reviewed, as are data speaking to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
475
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 652 publications
(505 citation statements)
references
References 68 publications
8
475
0
7
Order By: Relevance
“…27 There is some evidence that antibody-dependent cellular cytotoxicity mediated by activation of natural-killer cells contributes to the clinical response to rituximab. 28 Investigators have postulated that intensive chemotherapy could compromise the effi cacy of rituximab by impairing immune cellular mechanisms. 5 However, the results of our study do not favour such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…27 There is some evidence that antibody-dependent cellular cytotoxicity mediated by activation of natural-killer cells contributes to the clinical response to rituximab. 28 Investigators have postulated that intensive chemotherapy could compromise the effi cacy of rituximab by impairing immune cellular mechanisms. 5 However, the results of our study do not favour such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The CD20 antibody Rituximab was the first antibody approved for the treatment of cancer and is meanwhile an essential component of most treatment strategies for B-cell lymphoma [3]. The success of Rituximab has been attributed to several characteristics including its ability to mediate Fc receptor-dependent effector mechanisms, such as complementand antibody-dependent cellular cytotoxicity (ADCC) of NK cells [4]. Despite the undisputed success of Rituximab in lymphoma therapy, some patients do not respond at all, others for a limited time only.…”
Section: Introductionmentioning
confidence: 99%
“…Several new antibodies with enhanced effector functions demonstrated that in vitro tests have been developed (e.g., Ofatumumab, Ocrelizumab, Veltuzumab, AME-133V, PRO131921 and GA101) [23], but to date their clinical performances are disappointed in direct comparison with rituximab [25], and whether such new antibodies will be clinically superior to rituximab therapy remains to be seen [26]. In recent years, requirements for developing new antibodies to provide effective therapies for those patients who are insensitive or develop resistance to rituximab are increasingly urgent [23].…”
Section: Background 419mentioning
confidence: 99%